Alley-gates and domestic burglary: Findings from a longitudinal study in urban South Wales. (March 2018) - Rogers, Colin
The introduction of Crime Prevention Through Environmental design (CPTED) initiatives such as alley-gating is now widespread across the United Kingdom (UK), and has become part of the urban landscape. For practitioners and policy makers alike, erecting steel gates at entrances to alleys is seen as a major initiative for reducing domestic burglary. In particular, in the current climate of economic austerity, such apparently cost-effective measures may seem more attractive to policy makers and planners alike as they struggle to maintain public confidence in the criminal justice system and reduce levels of criminality. This paper examines one such alley-gate initiative at Cadoc, Barry, South Wales, based on 10 years of data collection, and considers the long-term impact upon recorded domestic burglary. It also probes local community perceptions of the gates in tackling the problem of crime.